The comparative study of single and two-phase models for magnetite nanofluid forced convection in a tube. (July 2015) - Hanafizadeh, P.; Ashjaee, M.; Goharkhah, M.; Montazeri, K.; Akram, M.
Abstract: The main aim of this study is to compare two-phase and single-phase approaches in simulating forced convective heat transfer of Fe3 O4 –water nanofluid in both developing and fully developed regions of a tube under constant heat flux. Three different two-phase models, namely, mixture, Volume of Fluid and Eulerian models have been utilized in the numerical analysis for the simulation of the nanofluids flow. In the single-phase models, four different correlations have been chosen for estimation of conductivity of nanofluid (constant, Maxwell, Brownian, proposed model). In order to validate single and two-phase simulations, an experimental setup is designed and fabricated. The experiments have been performed for nanofluids in volume fraction range of 0.5 to 2% and Reynolds number range of 300 to 1200 in the tube with the diameter and length of D = 0.0098 m, L = 2.375 m, respectively. Results of the two-phase models have been compared with that of the best single-phase model and the collected experimental data. It is concluded that considering the Brownian motion effect in the static Maxwell model significantly improves the accuracy. However, the presented correlations for thermal conductivity and viscosity lead to the closest results to the experimental data.